Pemberitaan Media Tentang Transgender Perempuan di Madura - Abdul Aziz; Mohammad Wardi (Universitas Muhammadiyah Sidoarjo, 2018)
This study focuses on the news about the existence of female transgender (transpuan) on the island of Madura, the news about transpuan Madura in different media, namely merdeka.com, okezone.com, suarajatimpost.com and suarapamekasan.com. The research method used in this research is the method of literature research, literature study on research dominated by non-field data collection. The results show first, the existence of transpuan in Madura in the public sphere is no longer seen as a marginal group. Secondly, Journalists from a number of media in charge of coverage in Madura, able to present objective values about the role of transpuan in the public sphere. Third, transpuan that was appointed to civil servants gives a picture to the public that gender is not a fundamental issue for the Maduranes as a minority and marginal groups that are considered outside the line of reasonableness.